Influência do manejo sobre espécies nativas com potencial madeireiro em sistemas agroflorestais no Portal da Amazônia - Martins, Cristiano Lima (Universidade Federal de São Carlos, 2021)
We evaluated functional attributes of fifteen native tree species with timber potential in multi-stratified and biodiverse agroforestry systems implanted and managed by farmers, in recent agroforestry movement, in three municipalities of Portal da Amazônia (MT – Brazil), to provide subsidies and discuss how growth conditions and management can affect the potential for wood production of these species. For this, we verified how the growth conditions (full light, half-light or shade) and the intensity of thinning and pruning management (absent, moderate, intense) affect the functional attributes related to productivity (diameter, height, volume and crown width) and stem quality of native wood species grown in thirteen agroforestry systems. Generalized mixed model and principal component analysis (PCA) were carried out to verify the relationship between the variables analyzed, the environmental conditions and intensity of management. The results showed that individuals with higher biomass increases in areas with more incidence of light. The management did not affect the stem quality for any of the selected species, and only 18% of the individuals had good stem quality. We grouped the species by their mean values of their functional attributes, and ranked the best for each management intensity. The most suitable species for areas poorly managed in relation to the stem quality were Colubrina glandulosa, Sterculia striata, Cedrella fissilis, Dipteryx odorata and Astronium urundeuva; for intensively managed areas were Schizolobium parahyba, Sterculia striata, Samanea tubulosa, Dipteryx odorata and Tabebuia Gomes ex DC. Complementary studies are needed on the effect of management and light requirement on agroforestry systems, to realize the wood potential of the species evaluated in this study.
Influence of management on native species growth in agroforestry systems in Portal da Amazonia region
Keywords: Silvicultura de espécies nativas; Produtos florestais madeireiros; Manejo florestal; Condição de crescimento; Silviculture of native species; Timber products; Forest management; Growth conditions; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL